Covid-19 pandemic-syndemia in America as of 08/30/2023 - Mora Alvarado, Darner (2024)
The present study describes the evolution of the Covid-19 pandemic-syndemic in America as of 08/30/2023, which covers from the declaration of the pandemic by the WHO on 03/11/2020, the declaration of the end of the health emergency on 05/06/2023 and a period of about four more months of endemicity, until the date of 08/30/2023. The results of the indicators of confirmed cases, cases per 100,000 inhabitants, deaths, deaths/million inhabitants, and fatality in the 35 countries, indicate that the most impacted nation is Peru with 6,565.65 deaths/million inhabitants. , followed by the USA with 3,391.83, Brazil 3,287.79, Chile with 3,160.80 and Trinidad and Tobago with 2,877.40/million inhabitants. The countries with the highest mortality rates are: Peru with 4.9%, Mexico 4.38%, Ecuador 3.37%, Trinidad and Tobago 2.79% and Paraguay 2.71%. In the case of Costa Rica, the deaths/million inhabitants was 1,820.08 with a fatality rate of 0.76%. On the other hand, an outstanding fact is that the nation with the most confirmed cases and deaths is the USA, with 103,436,829 and 1,127,152 respectively. However, the country most impacted in deaths/million inhabitants was Peru, as indicated above. However, it is recommended to establish a quantitative system using the values ​​of the indicators of the number of cases/100,000 inhabitants, deaths/100,000 inhabitants. and fatality rates, to identify the most impacted countries by continent and globally.